Basic Values, Ideological Self-Placement, and Voting: A Cross-Cultural Study. (October 2017) - Caprara, Gian Vittorio; Vecchione, Michele; Schwartz, Shalom H.; Schoen, Harald; Bain, Paul G.; Silvester, Jo; Cieciuch, Jan; Pavlopoulos, Vassilis; Bianchi, Gabriel; Kirmanoglu, Hasan; Baslevent, Cem; Mamali, Cătălin; et al.
The current study examines the contribution of left–right (or liberal–conservative) ideology to voting, as well as the extent to which basic values account for ideological orientation. Analyses were conducted in 16 countries from five continents (Europe, North America, South America, Asia, and Oceania), most of which have been neglected by previous studies. Results showed that left–right (or liberal–conservative) ideology predicted voting in all countries except Ukraine. Basic values exerted a considerable effect in predicting ideology in most countries, especially in established democracies such as Australia, Finland, Italy, United Kingdom, and Germany. Pattern of relations with the whole set of 10 values revealed that the critical trade-off underlying ideology is between values concerned with tolerance and protection for the welfare of all people (universalism) versus values concerned with preserving the social order and status quo (security). A noteworthy exception was found in European postcommunist countries, where relations of values with ideology were small (Poland) or near to zero (Ukraine, Slovakia).